2018
DOI: 10.1007/s00330-018-5437-8
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic accuracy of 3T magnetic resonance imaging in the preoperative localisation of parathyroid adenomas: comparison with ultrasound and 99mTc-sestamibi scans

Abstract: • PTA(s) quadrant localisation by 3TMRI was more accurate than US+99mTc-sestamibi. • MRI identified all enlarged glands in multiglandular disease similarly to US. • MRI identified 6/7 ectopic PTAs similarly to 99mTc-sestamibi. • Presurgical PTA(s) localisation by 3TMRI select the optimal candidates for MIP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(41 citation statements)
references
References 42 publications
0
40
0
1
Order By: Relevance
“…Argiro’ et al [ 47 ], for instance, found MRI more sensitive (97.8%) than US or 99mTc-MIBI, either alone (89.1% and 83.6%, respectively) or combined (93.4%), for the pre-surgical detection of benign parathyroid lesions, as well as for the diagnosis of multiglandular disease and ectopic parathyroid adenomas.…”
Section: Discussionmentioning
confidence: 99%
“…Argiro’ et al [ 47 ], for instance, found MRI more sensitive (97.8%) than US or 99mTc-MIBI, either alone (89.1% and 83.6%, respectively) or combined (93.4%), for the pre-surgical detection of benign parathyroid lesions, as well as for the diagnosis of multiglandular disease and ectopic parathyroid adenomas.…”
Section: Discussionmentioning
confidence: 99%
“…A marbled appearance can also sometimes be seen [100]. Following intravenous gadolinium contrast administration, rapid enhancement in the arterial phase is observed [101,102], which has been shown to increase diagnostic confidence [100,103]. Rarely, hemorrhage, fat (such as in a lipoadenoma) or fibrosis may result in atypical imaging features on MRI [98,100].…”
Section: Mrimentioning
confidence: 99%
“…In 2001, a commercial formulation, with specific use and indication for breast cancer diagnosis, became available, although it is currently discontinued. Since then, 99m Tc-sestamibi has been investigated as a diagnostic probe in several types of cancer, for mammary scintigraphy and parathyroid adenoma imaging [32–36]. The development of new techniques such as breast specific gamma imaging (BSGI) has revalued the usefulness of 99m Tc-sestamibi in oncology field [3740].…”
Section: Discussionmentioning
confidence: 99%